Management of Septic Mastitis in a Seven Months Old New Zealand White Rabbit Doe (Sahel Journal of Life Sciences FUDMA, 2025)
Mastitis is a condition affecting various animals, including rabbits, hamsters, mice, and rats. While these species are frequently used as models for studying mammary gland infections in biomedical research, there is limited understanding of their natural occurrence, epidemiology, and management. This case report focuses on the causes, clinical signs, pathology, and treatment of septic mastitis in rabbits, highlighting existing knowledge gaps and emphasising the need for further research. On 29th May, 2025, a client presented her seven-month-old New Zealand rabbit doe, weighing 2.5kg, to the University of Maiduguri Veterinary Teaching Hospital, complaining that she noticed a swollen mass on the rabbit's chest. Physical examination revealed an abscess on the first mammary gland located at the right anterior region of the doe; the mass was painful on touch and a dark brown necrotic tissue was seen on its medial aspect. Creamy-white viscous fluid was recovered on aspiration. A swab sample was collected from the affected area for bacterial culture. This was followed by differential diagnosis that included septic mastitis, cystic mastitis and caked mammary gland. Bacterial culture yielded a moderate growth of Staphylococcus aureus after 24 hours of incubation at 37ÂºC, confirming septic mastitis. Septic mastitis is a primary reason for culling adult does from commercial rabbit farms. It causes serious medical and reproductive challenges, but it is reversible if diagnosed and properly managed on time.